The Dynamics of Education in the Reactualization of Betawi Cultural Identity: The Roles of Family, School, and Community - Irfan, Ahmad; Setiady, Dicky; Setiyawan, Agus (Jurnal Pendidikan Islam, 2023)
Purpose – This article aims to explore the integrative role of family education, community, and school in the process of reactualizing the identity and cultural heritage of Betawi, focusing on two main questions: (1) How do family education, school, and community contribute to maintaining and promoting the Betawi culture? Moreover, (2) How do these three elements interact in reactualizing Betawi cultural identity?. Design/methods/approach – This study employs a qualitative approach, mainly historical research, to analyze the evolution and dynamics of Betawi culture. Data were collected through the study of historical and contemporary documents and group discussion forums with experts in Betawi history and culture. The data analysis was conducted using Miles and Huberman's method. Findings – The research reveals that family education, schools, and communities play a significant role in maintaining and promoting Betawi culture. Families contribute to teaching language and customs, schools provide formal education about the history and culture of Betawi, and communities strengthen cultural practices through social and communal activities. This study also highlights the richness and complexity of Betawi culture, consisting of various elements such as language, livelihoods, social systems, occupations, education, beliefs, and arts. Research implications – The findings of this study offer valuable insights into the importance of a multidimensional approach in understanding and preserving Betawi culture. These findings affirm the crucial roles of family education, schools, and communities as integral components in actualizing cultural identity, especially amid the challenges of globalization and modernization. The study also suggests the need for more integrated and comprehensive cultural preservation strategies, considering the influence of history, location, language, and religion.